Validation of a Portable Blood Gas Analyzer for Use in Challenging Field Conditions at High Altitude - Nawrocki, Janek; Furian, Michael; Buergin, Aline; Mayer, Laura; Schneider, Simon; Mademilov, Maamed; Bloch, Madeleine S.; Sooronbaev, Talant M.; Ulrich, Silvia; Bloch, Konrad E. (Frontiers in Physiology, 2021)
Background: Novel, portable blood gas analyzers (BGA) may serve as essential point-of-care tools in remote regions, during air travel or in ambulance services but they have not been extensively validated. Research question: We compared accuracy of a portable BGA to a validated sta-tionary device. Methods: In healthy individuals and patients with chronic obstructive pulmonary disease participating in clinical field studies at different altitudes, arterial blood sam-ples were obtained at rest and during exercise in a hospital at 760m and in a high altitude clinic at 3100m. Paired measurements by a portable BGA (EPOC, Siemens Healthcare) and a stationary BGA (Rapidpoint500, Siemens Healthcare) were per-formed to compute bias (mean difference) and limits of agreement (95% CI of bias). Results: Of 105 individuals, 248 arterial blood samples were analyzed, 108 at 760m, 140 at 3100m. Ranges of values measured by portable BGA were: pH 7.241-7.473, PaCO2 21.5-52.5mmHg, PaO2 45.5-107.1mmHg. Bias (95%CI) between devices were: pH 0.007 (-0.029 to 0.044), PaCO2 -0.3mmHg (-4.8 to 4.2) and PaO2 -0.2 mmHg (-9.1 to 4.7). For pH, agreement between devices was improved by the equation to correct pH by portable BGA = -1.37+pHmeasured*1.19; bias after correction -0.007 (-0.023 to 0.009). The portable BGA was easily handled and worked reliably. Interpretation: Accuracy of blood gas analysis by the portable BGA in comparison to the reference BGA was adequate for clinical use. Because of portability and ease of handling, portable BGA are valuable diagnostic tools for use in everyday practice as well as under challenging field conditions.